18F-FP-CIT Positron Emission Tomography for Correlating Motor and Cognitive Symptoms of Parkinson's Disease - Yang, YoungSoon (Dement Neurocogn Disord, 2017)
BACKGROUND AND PURPOSE: The aim of this paper was to investigate the utility of 18F-N-(3-fluoropropyl)-2β-carboxymethoxy-3β-(4-iodophenyl) nortropane (FP-CIT) positron emission tomography (PET) for evaluating the severity of Parkinson's disease (PD) according to various clinical stages, and to identify the relationship between the striatal substructure and the Unified Parkinson's Disease Rating Scale (UPDRS) motor score, cognitive symptoms through 18F-FP-CIT PET. METHODS: We retrospectively identified 542 patients with various clinical stages of PD who underwent an 18F-FP-CIT PET at our clinics. The difference between the 18F-FP-CIT PET according to the Hoehn-Yahr stage, correlation between 18F-FP-CIT PET and the UPDRS III grouped motor items, and the Korean Mini-Mental State Examination (K-MMSE) were investigated. RESULTS: As disease progressed, the right caudate and both the anterior putamen and caudate/putamen ratios exhibited a significantly lower uptake. The uptake of all striatal substructures was significantly correlated with the UPDRS total motor score. The right caudate nucleus was significantly related to both the UPDRS tremor items and the right UPDRS akinesia-rigidity items. The left caudate nucleus was related to both the UPDRS tremor items and UPDRS akinesia-rigidity items. The right anterior putamen was related to the axial items, right tremor and akinesia-rigidity items; while the left anterior putamen was related to the right tremor and right akinesia-rigidity items. Both of the posterior putamens were related to the axil items, left tremor and left akinesia rigidity items. K-MMSE was not significantly related to any striatal substructures. CONCLUSIONS: The UPDRS total motor score was significantly correlated with the uptake of all striatal substructures. However, the 18F-FPCIT uptake in specific striatal substructures was rather complexly correlated with the UPDRS motor grouped items and was not significantly related to K-MMSE. These results suggest the possibility of the complex pathophysiology of motor symptoms of PD and limitation of 18F-FPCIT PET for the evaluation of the severity of PD motor and cognitive symptoms.